POTENSI PENULARAN MALARIA PADA PRAJURIT TENTARA NASIONAL INDONESIA (STUDI PADA BATALYON INFANTRI 411 KOTA SALATIGA) - Diana Andriyani Pratamawati; Riyani Setiyaningsih; Kusno Barudin; Lulus Susanti; Widiarti Widiarti (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
Since 2016, there has been an increase in cases of malaria sufferers mostly from the Army Infantry Battalion 411 Pandawa based in Salatiga City. Based on data from the Salatiga District Health Service, number of cases reached 93 people who were positively malaria in 2016 and 84 positive cases in 2017. The purpose of this study was to determine the potential for malaria transmission to the the Indonesian Armed Forces (TNI) 411 Pandawa Battalion in Salatiga City. This research was a descriptive analytic type research with crossectional approach. The results of the study obtained a blood sample of 66 people and were willing to be interviewed. Chi-square test results are known to travel outside the area significantly associated with the incidence of malaria with a value of p <0,05. The results of this study interview, most of the soldiers were exposed to malaria while serving in the inland of Papua Province, in 2015. The results of blood tests found the Plasmodium vivax malaria parasite with a young trophozoite stage in the blood of three soldiers. The potential for transmission in the Infantry Battalion 411 in Salatiga City is nothing and the location of the soldier's dormitory does not reseptive because there are no malaria vectors.